Experimental behavior of mesh reinforced shotcrete and steel fiber reinforced shotcrete panels - Barros, Joaquim A. O. (1998)
The existent experimental data reveal that the steel fiber reinforcement improves the energy absorption capacity, the fatigue and impact strength and the cracking behavior of the cement based materials. These material benefits increase the structural ductility, safety and durability. Apart from these material-structural enhancements, the applications made by the steel fiber reinforced shotcrete (SFRS), like the tunnel linings, have proven that SFRS can provide a viable technical, economical and practical alternative to conventional mesh reinforced shotcrete. The loss of concrete and the construction time decrease when using SFRS technology. In order to compare the behavior of the conventional mesh reinforced shotcrete and SFRS it is current to carry out experimental tests on panels of these materials. In this article, the tests performed on panels of concrete reinforced with wire mesh and on panels reinforced with three different percentages of hooked-ends steel fibers (25, 30 and 35 kg/m3 of fibers) are discribed. All the panels were manufactured by shotcrete technology in the site plant of the Alqueva dam (Portugal). The main results are presented and analyzed.